1992
DOI: 10.1200/jco.1992.10.11.1762
|View full text |Cite
|
Sign up to set email alerts
|

Medical Research Council prospective study of surveillance for stage I testicular teratoma. Medical Research Council Testicular Tumors Working Party.

Abstract: This study confirms the safety of surveillance as a method of management and identifies a group of patients with a high risk of relapse. A prospective phase II study has been initiated to determine whether two courses of platinum-based adjuvant chemotherapy will prevent relapse in these high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
211
0
6

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 399 publications
(223 citation statements)
references
References 9 publications
6
211
0
6
Order By: Relevance
“…In the original prospective study, 80% (of 100 relapses) occurred within the first year (54 of these in the first 6 months) and 92% by 2 years (Read et al, 1992). A number of subsequent studies have demonstrated similar results and are summarised in Table 1.…”
Section: Stages Iic -Ivmentioning
confidence: 82%
See 1 more Smart Citation
“…In the original prospective study, 80% (of 100 relapses) occurred within the first year (54 of these in the first 6 months) and 92% by 2 years (Read et al, 1992). A number of subsequent studies have demonstrated similar results and are summarised in Table 1.…”
Section: Stages Iic -Ivmentioning
confidence: 82%
“…Surveillance as a strategy for the management of stage I tumours was prospectively studied by the Medical Research Council and their results were published in 1992 (Read et al, 1992). In the absence of high-risk features where relapse rates approach 50%, among the usual population undergoing surveillance a relapse rate of around 20% is to be expected.…”
Section: Stages Iic -Ivmentioning
confidence: 99%
“…Presence of embryonal cell carcinoma, absence of endodermal sinus tumour and invasion of tumour cells into blood and lymphatic vessels have been found to be predictors of relapse [1,12,13]. Subsequent studies have shown that vascular invasion (VI) is the single most important prognostic factor regarding risk of relapse [14][15][16][17].…”
Section: Prognostic Risk Factorsmentioning
confidence: 99%
“…Subsequent studies have shown that vascular invasion (VI) is the single most important prognostic factor regarding risk of relapse [14][15][16][17]. Without adjuvant treatment, the high-risk group (VI positive) has a 3-year relapse rate of approximately 50%, while low-risk patients (VI negative) have a relapse risk of 10 to 20% [1,3,[16][17][18][19][20][21][22].…”
Section: Prognostic Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation